Decorporation potential of lansoprazole against radiothallium (201Tl) in internally contaminated BALB/c mice and New Zealand White rabbits. (January 2019) - Nishad, DK; Rawat, HS; Singh, T; Bhatnagar, A; Mittal, G
Introduction: This study examined the decorporation potential of lansoprazole (LNP) as radioactivity decorporation agent for radiothallium ( 201 Tl) in internally contaminated BALB/c mice and New Zealand White rabbits using radiometry and gamma scintigraphy. Methods: Animals were divided into three groups, that is, control, pretreatment-1 (1X LNP), and pretreatment-2 (2X LNP). Mice received LNP intraperitoneally, while in rabbits LNP was given through oral route 0.5 and 1.5 h before radiothallium administration, respectively. Mice and rabbits used in the experiment were administered 1.48 and 11.1 MBq radiothallium ( 201 TlCl) through intravenous and oral route, respectively. Once started as prophylactic, LNP was continued as therapeutic twice a day till the end of study period. Radiometry and gamma scintigraphy were used to monitor radiothallium retention and uptake patterns in animals. Gamma scintigraphic images of rabbits were taken at different time intervals up to 72 h and were analyzed for comparative uptake pattern of 201 TlCl in all the groups. Results: LNP treatment significantly increased the 201 Tl elimination over untreated control and considerably reduced the retention of 201 Tl in various tissues and organs. Decrease in radiothallium uptake up to 40% was observed in LNP-treated mice as compared to untreated control. While in rabbits, whole-body radioactivity burden at 72 h was found to be 31.24%, 26%, and 18.54% in untreated control, 9 and 18 mg/kg LNP-treated groups, respectively. Conclusion: LNP exhibited dose-dependent decorporation potential to effectively enhance the elimination of 201 Tl in mice and rabbits experimentally contaminated with 201 TlCl.